Biomimetic and biodegradable cellulose acetate scaffolds loaded with dexamethasone for bone implants - Tsiapla, Aikaterini-Rafailia; Karagkiozaki, Varvara; Bakola, Veroniki; Pappa, Foteini; Gkertsiou, Panagiota; Pavlidou, Eleni; Logothetidis, Stergios (Beilstein Journal of Nanotechnology, 2018)
There is, as a matter of fact, an ever increasing number of patients requiring total hip replacement (Pabinger, C.; Geissler, A. Osteoarthritis Cartilage 2014, 22, 734–741). Implant-associated acute inflammations after an invasive orthopedic surgery are one of the major causes of implant failure. In addition, there are instability, aseptic loosening, infection, metallosis and fracture (Melvin, J. S.; Karthikeyan, T.; Cope, R.; Fehring, T. K. J. Arthroplasty 2014, 29, 1285–1288). In this work, a drug-delivery nanoplatform system consisting of polymeric celluloce acetate (CA) scaffolds loaded with dexamethasone was fabricated through electrospinning. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) indicated the successful fabrication of these structures. Cytotoxicity studies were performed by using MTT assay, methylene-blue staining and SEM fixation and showed very good cell adhesion and proliferation, indicating the cytocompatibility of these fibrous scaffolds. Drug-release kinetics was measured for the evaluation of a controllable and sustained release of anti-inflammatory drug onto the engineered implants and degradation study was conducted in order to assess the mass loss of polymers. This drug-delivery nanoplatform as coating on titanium implants may be a promising approach not only to alleviate but also to prevent implant-associated acute inflammations along with a simultaneous controlled release of the drug.
Keywords: drug delivery; electrospinning; nanocoatings; orthopedics; tissue engineering